2006
DOI: 10.2106/jbjs.e.00007
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Proteolytic Enzyme Serratiopeptidase in the Treatment of Experimental Implant-Related Infection

Abstract: Serratiopeptidase was effective for eradicating infection caused by biofilm-forming bacteria in this experimental animal model. The antibiofilm property of the enzyme may enhance antibiotic efficacy in the treatment of staphylococcal infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(22 citation statements)
references
References 20 publications
0
22
0
Order By: Relevance
“…The emergence of antibiotic-resistant bacteria has led investigators to attempt to develop antibiotic-independent mechanisms to impair bacterial ability to form biofilm. 17,18 In S. epidermidis modulation of icaADBC expression, which promotes PIA-mediated biofilm, represents an attractive therapeutic target in this context.…”
Section: Discussionmentioning
confidence: 99%
“…The emergence of antibiotic-resistant bacteria has led investigators to attempt to develop antibiotic-independent mechanisms to impair bacterial ability to form biofilm. 17,18 In S. epidermidis modulation of icaADBC expression, which promotes PIA-mediated biofilm, represents an attractive therapeutic target in this context.…”
Section: Discussionmentioning
confidence: 99%
“…Kokai-Kun et al (2009) showed that lysostaphin administered at 15 mg/kg in combination with 50 mg/kg nafcillin, three times per day for four days in mice, eradicated S. aureus biofilms from implanted catheters and eliminated heart and liver infections in S. aureus-infected mice (Kokai-Kun et al 2009). Mecikoglu et al (2006) showed that serratiopeptidase was effective for eradicating infection caused by biofilm-forming bacteria, and also that the anti-biofilm property of the enzyme may enhance antibiotic efficacy in the treatment of staphylococcal infections (Mecikoglu et al 2006). The different results found in the present study could be due to the type of enzyme.…”
Section: Discussionmentioning
confidence: 64%
“…The biofilm matrix is a collection of polysaccharides, proteins, nucleic acids, glycoproteins and phospholipids (Czaczyk and Myszka 2007). With this in mind, it is clear that enzymes can be used for degradation of biofilm (Johansen et al 1997;Berg et al 2001;Mecikoglu et al 2006;Lu and Collins 2007;Chaignon et al 2007). Enzymatic activity can be directed to the biofilm matrix, allowing better penetration of the subsequent antimicrobial agents used or can be targeted towards pathogen cell wall components in order to cause their lysis (Johansen et al 1997;Kaplan et al 2004).…”
Section: Original Papermentioning
confidence: 99%
“…Thus, serratiopeptidase has anti-inflammatory, analgesic, anti-edemic, antipathogenic, fibrinolytic and caseinolytic properties. In contradiction, Joshi and Nerurkar et al [27] conducted a study on rats (paw model) to evaluate the efficacy of serratiopeptidase in reducing edema. They concluded that serratiopeptidase was not an effective anti-inflammatory agent either alone or with diclofenac and further studies had to be done in humans.…”
Section: Mechanism Of Actionmentioning
confidence: 99%